Astrocyte‐Predominant Tau Pathology in a Patient With VCP R191Q Variant - Daisuke Taniguchi; Ko Tsuyama; Taku Hatano; Karin Ashizawa; Takashi Yao; Motoki Fujimaki; Kazuaki Kanai; Yuanzhe Li; Manabu Funayama; Nobutaka Hattori (Neuropathology, 2026)
ABSTRACT Variants in the valosin‐containing protein (VCP) gene cause multisystem proteinopathy, typically characterized by TDP‐43 pathology. However, there are few reports describing tau pathology in VCP variant carriers. Here, we report a Japanese woman carrying a heterozygous VCP R191Q variant, who developed progressive muscle weakness, frontotemporal dementia, and parkinsonism beginning in her mid‐forties and died at the age of 61. Neuropathological examination demonstrated FTLD‐TDP type D pathology involving the frontal and temporal cortices, limbic structures, brainstem, spinal cord, and skeletal muscle. In addition, a distinct pattern of tau pathology was identified, predominantly in astrocytes and extending from the lower brainstem throughout the spinal cord. Tau aggregates were distributed in perivascular, subpial, and central gray matter, with a rostrocaudal distribution. Immunohistochemistry and confocal microscopy demonstrated colocalization of 3‐repeat (3R) and 4‐repeat (4R) tau within astrocytes, with predominance of 3R tau. Western blot analysis confirmed these findings and showed a tau banding pattern similar to that in Alzheimer's disease. These features differ from those observed in disorders with astrocytic tau pathology, such as cervical spondylotic myelopathy, chronic traumatic encephalopathy, and aging‐related tau astrogliopathy, which are typically characterized by predominance of 4R tau and minimal or absent 3R tau involvement. They also differ from the neuronal tau pathology observed in the frontotemporal cortex in patients with the VCP D395G variant. This case expands the neuropathological spectrum of VCP‐related diseases and suggests a possible association between VCP variants and pathological tau aggregation.